Analysis of virulence profiles in clinical isolates of Klebsiella pneumoniae from renal abscesses: clinical significance of hypervirulent isolates - Lee, Jaehyeon; Hwang, Jeong-Hwan; Yeom, Ji Hyun; Lee, Sik; Hwang, Joo-Hee (Frontiers in Cellular and Infection Microbiology, 2024)
Klebsiella pneumoniae can cause a wide range of infections. Hypervirulent K. pneumoniae (hvKp), particularly associated with the K1 and K2 capsular types, is an increasingly significant microorganism with the potential to cause invasive infections, including renal abscesses. Despite the rising prevalence of hvKp infections, information on renal abscesses caused by K. pneumoniae is limited, and the clinical significance of hvKp associated with specific virulence genes remains elusive. This study performed at a 1200-bed tertiary hospital sought to identify the clinical and microbiological characteristics of renal abscesses caused by K. pneumoniae, focusing on various virulence genes, including capsular serotypes and multilocus sequence typing (MLST). Over an 8-year period, 64 patients with suspected renal abscesses were reviewed. Ten patients diagnosed with K. pneumoniae-related renal abscesses were ultimately enrolled in the study. Among the isolates from the 10 patients, capsular serotype K2 was predominant (40.0%), followed by K1 (30.0%). The most common sequence type by MLST was 23 (40.0%). In particular, six patients (60.0%) harbored specific genes indicative of hvKp: iucA, peg-344, rmpA, and rmpA2. These findings highlight the importance of hvKp as a pathogen in renal abscesses. Although the nature of hvKp is relatively unknown, it is widely recognized as a highly virulent pathogen that can infect relatively healthy individuals of various ages and simultaneously cause infections at multiple anatomical sites. Therefore, when treating patients with K. pneumoniae-related renal abscesses, caution is necessary when considering the characteristics of hvKp, such as potential bacteremia, multi-organ abscess formation, and metastatic spread.